Die gebruik van die Ou Testament in die beg ronding van die kerk se kultuurtaak - "n hermeneutiese probleem - Breytenbach, Andries (Hervormde teologiese studies, 1996)
The use of the Old Testament in motivating the church's responsibility towards the social order - a hermeneutical issue. The conviction within the ranks of the Nederduitsch Hervormde Kerk van Afrika that the church has a responsibility with regard to the social order is strongly based on a reading of the Old Testament which can be traced back to Calvin. The hermeneutics underlying this kind of reading of the Old Testament basically works with a 'deeper' meaning - a meaning which can be brought to light by means of typological exegesis. The author argues that this kind of hermeneutics cannot be maintained in the aftermath of historical-critical research. The argument is put forward that the church does not have a responsibility when it comes to the structuring of society. The theological position of the author is one which links up with qialectical theology.